Pengaruh Volatilitas Harga Saham, Volume Perdagangan Saham dan Free Cash Flow terhadap Return Saham - City Nurdiansyah; Indawati Indawati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of stock price volatility, trading volume, and free cash flow on stock returns of consumer non-cyclical sector companies listed on the Indonesia Stock Exchange during 2019–2023. A quantitative method with secondary data collected from the IDX official portal was employed. Data analysis was conducted using EViews 12 through a panel data regression model with a Random Effect Model (REM) approach. The results indicate that, simultaneously, all three independent variables significantly influence stock returns. Partially, however, only trading volume shows a significant impact, while stock price volatility and free cash flow do not significantly affect returns individually. The adjusted R-squared value of 0.172387 reveals that approximately 17.2% of stock return variation is explained by these variables. These findings support the signaling theory, suggesting that trading activity reflects investors’ responses to firms’ financial information. This study contributes to investors and academics in understanding how technical and fundamental factors interact to influence stock performance in a relatively stable sector.